Preparation of dihydroquinazoline carbohydrazone Fe(ii) complexes for spin crossover. (14th March 2016) - Shen, Fu-Xing; Huang, Wei; Yamamoto, Takashi; Einaga, Yasuaki; Wu, Dayu
Abstract : Mononuclear spin-crossover complexes of dihydroquinazoline derivatives were synthesized to enable the spin crossover phenomenon via the variation of the solvent, anion and substituent. Abstract : Dihydroquinazoline Fe II complexes, namely [Fe(pq-R )2 ](X)2 · x CH3 OH· y CH3 CN· z H2 O (R = 2-py: X = ClO4 −, x = 1, y = 0, z = 2 (1 ), BF4 −, x = 0, y = 2, z = 1.75 (2 ), CF3 SO3 −, x = 1, y = 1, z = 0 (3 ); and X = ClO4 − : R = 2-OCH3, x = 0, y = 0, z = 1 (4 ), R = 3-OCH3, x = 0, y = 0, z = 1 (5 )), were prepared and the effects of the solvent, counteranion and ligand substituent on spin crossover properties were discussed. Comparison of X-ray diffraction data for these complexes revealed the sole presence of high-spin Fe II at 298 K and the bond distances around the Fe II center at low temperature fall much closer to those at high temperature, which is consistent with variable-temperature dc magnetic susceptibility data. However, the loss of solvent induced a significant change in the spin state of complexes1 and2 . Moreover, fits to magnetic data of the desolvated samples provide crossover temperatures of T 1/2 = 182.9(6), 157.0(8) and 138.3(5) K for1-des (ClO4 − ), 2-des (BF4 − ) and3-des (CF3 SO3 − ), respectively, indicative of the anion-dependent transition temperature. The cooperativity operating in the complexes is thought to be mainly from the intermolecular π⋯π interactions between dihydroquinazoline rings on the neighboring molecules. The ligand substituent effect was also investigated on Fe II SCO properties. This work revealed the spin crossover properties of new types of dihydroquinazoline Fe(ii ) complexes, including the transition temperature, the degree of completion and the cooperative nature of the transition, which can be optimally designed when developing new spin-crossover materials.